2013
DOI: 10.1044/1092-4388(2012/12-0036)
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Stuttering Interventions for Children and Adolescents: A Systematic Review and Meta-Analysis

Abstract: Conclusions drawn from the extant research suggest that data to support the efficacy of behavioral intervention in children exists for a limited number of intervention strategies, based on a meager number of methodologically acceptable studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(53 citation statements)
references
References 30 publications
1
41
0
5
Order By: Relevance
“…Treatments for stuttering in school aged children seem to be less efficacious. 55 Preparation • Is he or she able to understand what you and others say to him or her?…”
Section: Stutteringmentioning
confidence: 99%
“…Treatments for stuttering in school aged children seem to be less efficacious. 55 Preparation • Is he or she able to understand what you and others say to him or her?…”
Section: Stutteringmentioning
confidence: 99%
“…These treatments have encompassed diverse techniques from the use of carbon dioxide, or pharmacological interventions, to those that are behaviourally based. Recent published reviews of stuttering interventions have included: Nye et al (2013), which evaluated the effectiveness of nine studies reporting behavioural interventions for children and adolescents; Blomgren (2013), which provided an overview of selected approaches to interventions with children and adults; Sidavi and Fabus (2010), which summarized the literature on interventions with pre-school and elementary school-age children; Blomgren (2010), which provided an overview of treatment approaches for adults; Lincoln et al (2006), which examined the use of altered auditory feedback; Herder et al (2006), which reports a systematic review and meta-analysis of behavioural stuttering treatments; and Bothe et al (2006aBothe et al ( , 2006b, which carried out systematic reviews of behavioural treatment studies and pharmacological interventions published up to 2005. These reviews have highlighted the increasing size of the literature, and the wide variety of approaches that exist.…”
Section: Introductionmentioning
confidence: 99%
“…Interventions for children may be also divided into either direct approaches which intervene with the child, or indirect approaches which target family interactions. Existing reviews have identified evidence of treatment effectiveness for behavioural interventions across adults and children (Nye et al 2013, Blomgren 2013, Bothe et al 2006a. Treatment involving response-contingent principles in particular has been recommended for children, and the use of combined approaches with adults (Bothe et al 2006a).…”
Section: Introductionmentioning
confidence: 99%
“…• In children, strong evidence supports the Lidcombe method, which is based on the principle of operant learning and is delivered in constant collaboration with the parents (28)(29)(30)(31). Fluent speech is positively reinforced, and if stuttering events occur these are gently corrected.…”
Section: Therapymentioning
confidence: 95%